Chemical and isotopic changes in surface and underground waters in a Watershed in the Central Amazon - Alexandre Souza Bastos; Sávio José Filgueiras Ferreira; Didier Gastmans; Elaine Pires de Freitas; Alderlene Pimentel de Brito; Claudenilson Nogueira de Almeida; Sergio Duvoisin Junior (Revista Brasileira de Recursos Hídricos)
ABSTRACT Environmental monitoring of water is essential for efficient management of water source conservation in river basins. However, there is a lack of studies with this synergy applying unconventional techniques. We evaluated chemical characteristics of surface and underground waters (2021-2022), including for the first time the analysis of the isotopic composition of waters collected from water sources throughout Educandos`s Basin, in the city of Manaus-AM/Brazil, to evaluate chemical-isotopic changes in the view of anthropogenic impacts. Statistical analyzes were used to compare means, graphical analyzes and Principal Component Analysis to identify the main patterns of the data sets. Our results demonstrated a significant increase in pH, electrical conductivity and an increased in nitrates in polluted groundwater and reduced DO in contaminated surface waters. Furthermore, the isotopic signature did not indicate pollution through changes in the isotopic composition of natural and polluted waters, however, it showed more depleted signatures in one of the underground monitoring wells, indicating an impact site vulnerable to the interaction of aquifer waters with Rio Negro and Igarapé. When analyzing chemical parameters with isotopic composition, it can be allowed a better understanding of the mechanisms of circulation and mineralization of underground and surface waters in the Urban Hydrographic Basin.